Th. Dobzhansky and the development of evolutionary biology in the USSR. (September 2019) - Konashev, Mikhail B.
Th. Dobzhansky played a special role in the reception and development of the "synthetic theory of evolution, " as well as in the establishment of scientific connections between Soviet and U.S. evolutionists, and first and foremost, geneticists. These connections greatly influenced the development of Soviet genetics, of evolutionary theory and evolutionary biology as a whole, and in particular the restoration of Soviet genetics in the late 1960s. A discussion of Dobzhansky's correspondence and collaboration with colleagues in his native country, moreover, allows for an improved understanding of the complex and dramatic history of Soviet genetics and evolutionary theory. It also provides novel insights into the interactions between scientists and authorities in the Soviet Union (USSR).